Variations in serum sphingolipid levels associate with liver fibrosis progression and poor treatment outcome in hepatitis C virus but not hepatitis B virus infection. Issue 3 (28th January 2015) - Grammatikos, Georgios; Ferreiros, Nerea; Bon, Dimitra; Schwalm, Stephanie; Dietz, Julia; Berkowski, Caterina; Fitting, Daniel; Herrmann, Eva; Zeuzem, Stefan; Sarrazin, Christoph; Pfeilschifter, Josef
Abstract : Ablation of very‐long‐chain ceramides (Cers) with consecutive elevations in sphinganine levels has been shown to cause a severe hepatopathy in a knockout mouse model. We have recently shown that serum sphingolipids (SLs) are deregulated in patients with chronic liver disease. However, their role as possible biomarkers in liver fibrosis remains to date unexplored. We assessed, using liquid chromatography/tandem mass spectrometry, serum concentrations of various SL metabolites in 406 patients with chronic viral hepatitis, 203 infected with genotype 1 hepatitis C virus (HCV) and 203 with hepatitis B virus (HBV), respectively. We observed significant variations of serum SLs, with sphingosine and sphinganine being, both in univariate ( P < 0.05) as well as in multivariate analysis, significantly associated to severity of liver fibrosis in HCV‐infected patients (odds ratio [OR]: 1.111; confidence interval [CI]: 1.028‐1.202; P = 0.007 and OR, 0.634; CI, 0.435‐0.925; P = 0.018, respectively). Serum SLs correlated significantly with serum triglyceride and cholesterol levels as well as with insulin resistance, defined by the homeostatic model assessment index, in HCV patients. Sustained viral response rates in HCV patients were independently predicted by serum C24Cer (OR, 0.998; CI, 0.997‐0.999; P = 0.001), its unsaturated derivative C24:1Cer (OR, 1.001; CI, 1.000‐1.002; P = 0.059), and C18:1Cer (OR, 0.973; CI, 0.947‐0.999; P = 0.048), together with ferritin (OR, 1.006; CI, 1.003‐1.010; P < 0.001), alkaline phosphatase (OR, 1.020; CI, 1.001‐1.039; P = 0.032), and interleukin‐28B genotype (OR, 9.483; CI, 3.139‐28.643; P < 0.001). Conclusion : Our study demonstrates a tight interaction between variations in serum SL levels and progression of liver fibrosis as well as responsiveness to antiviral therapy. Particularly, sphingosine, sphinganine, and C24Cer appear as promising novel biomarkers in chronic HCV infection and should be further evaluated within the noninvasive prediction of liver fibrosis. (Hepatology 2015;61:812–822)